Examination of stress coping strategies as predictors of academic performance among students in teacher training colleges in central region Kenya - Muema, Elizabeth Ndinda; Muola, James; Muriungi, Pamela (EPRA International Journal of Multidisciplinary Research, 2020)
Despite the very high stake placed on education, poor academic performance has continued to be felt in Kenya in Primary Teacher Training colleges in Kenya. This affects the life and career progression of the students and becomes a challenge to both the parents and the nation at large. The study sought to establish how stress coping strategies predict academic performance among students in Primary Teacher Training Colleges in central region. Questionnaire on coping strategies was adapted from CISS-21 by endler and Parker. Academic Performance was inferred from the students mean grade obtained from the Mid-course examinations at the end of year one. Quantitative data was analyzed using SPSS version 26. To examine the relationships among the variables Pearson Product Moment Correlation Coefficient and regression analysis were used. Generally there was a negative significant correlation between the overall measure of Coping strategies ( r = 0.-56, p <0.01, n=197) .Academic performance was found to be significantly correlated with a) task oriented coping at (r = 0.68,p <0.01, n=197),b) emotional oriented coping( r = 0.-75,p,<0.01) and c) avoidance oriented coping (r=0.-68 ,p,<0.01).On regression analysis, Coping strategies had a significant predictive weight on academic performance (F,1,195)=89.5,p<0.0) with use of emotion and avoidance coping significantly predicting academic performance. Based on the findings it was recommended that educators, lecturers and other education stakeholders should create an enabling environment in order to enhance students’ academic self-efficacy, response to stressful situations and coping strategies. Students support services like guidance and counselling should be strengthened, and is important for the colleges to have intervention programs to buffer the negative impact of stressful environments and enhance positive coping strategies.
Keywords: Coping Strategies; Task oriented; Emotion oriented; Avoidance oriented; Performance; Teacher Training Colleges